Neuroprotective Effects of Eugenol Acetate Against Ischemic Stroke - Chen L; Zhang R; Xiao J; Liang Y; Lan Z; Fan Y; Yu X; Xia S; Yang H; Bao X; Meng H; Xu Y; et al. (Journal of Inflammation Research)
Liqiu Chen,1,2,* Ran Zhang,1,2,* Jing Xiao,1,2,* Ying Liang,1,2 Zhen Lan,3 Yingao Fan,2 Xi Yu,2 Shengnan Xia,2– 5 Haiyan Yang,2– 5 Xinyu Bao,2– 5 Hailan Meng,1– 6 Yun Xu,1– 6 Linjie Yu,1– 6 Xiaolei Zhu1– 6 1Department of Neurology, Nanjing Drum Tower Hospital, Clinical College of Nanjing University of Chinese Medicine, Nanjing, 210008, People’s Republic of China; 2Department of Neurology, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, 210008, People’s Republic of China; 3Department of Neurology, Nanjing Drum Tower Hospital, Clinical College of Nanjing Medical University, Nanjing, 210008, People’s Republic of China; 4State Key Laboratory of Pharmaceutical Biotechnology and Institute of Translational Medicine for Brain Critical Diseases, Nanjing University, Nanjing, 210008, People’s Republic of China; 5Jiangsu Provincial Key Discipline of Neurology, Nanjing, 210008, People’s Republic of China; 6Nanjing Neurology Medical Center, Nanjing, 210008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linjie Yu; Xiaolei Zhu, Department of Neurology, Nanjing Drum Tower Hospital, Clinical College of Nanjing University of Chinese Medicine, Nanjing, 210008, People’s Republic of China, Email yulinjie126@126.com; zhuquelee@126.comObjective: To explore the neuroprotective effect of Eugenol Acetate (EA) on post-stroke neuroinflammation and investigate the underlying mechanisms.Methods: For in vitro experiments, primary microglia were pre-incubated with EA for 2 hours, followed by lipopolysaccharide (LPS) stimulation for 24 hours or Oxygen-Glucose Deprivation (OGD) treatment for 4 hours. Real-time quantitative PCR, enzyme-linked immunosorbent assay (ELISA) and Western blot were performed to examine the expression levels of inflammatory cytokines in primary microglia. The activation of NF-κB signaling pathway was evaluated by immunofluorescence staining and Western blot. For in vivo experiments, middle cerebral artery occlusion (MCAO) was constructed to mimic ischemic brain injury on 8-week-old male C57BL/6J mice. The mice were continuously injected intraperitoneally with EA or vehicle after MCAO. Neurobehavioral tests and TTC staining were conducted to estimate the neurological deficits and infarct area. Moreover, the white matter integrity after MCAO was observed via immunofluorescence staining.Results: EA significantly reduced the expression of pro-inflammatory cytokines in LPS or OGD treated primary microglia, and inhibited LPS-induced activation of the NF-κB signaling pathway. In addition, EA alleviated ischemic brain injury and improved neuromotor function of MCAO mice. Furthermore, long-term neurological deficits and white matter integrity were improved by EA treatment after MCAO.Conclusion: EA alleviated ischemic injury and restored white matter integrity in MCAO mice, which might be associated with the inhibition of NF-κB signaling pathway in microglia. Therefore, EA might be a promising candidate for the treatment of ischemic stroke.Keywords: Eugenol Acetate, Ischemic Stroke, Neuroinflammation, NF-κB Signaling Pathway